The THE EFFECT OF EXCHANGE RATE, NET INCOME, CASH FLOW, TOTAL ASSETS ON STOCK PRICES IN THE MANUFACTURING SECTOR IN THE INDONESIA STOCK EXCHANGE, 2016-2020 - Wirda Lilia Wirda; Theonaldi Surya Halim; Angel Angel; Vanessa Vanessa (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2023)
Stock price is a constitution for investors to invest in the company, this study examines is to analyze the effect of exchange rate, net profit, cash flow, total assets on stock prices in manufacturing companies. The company has increased every year but it does not affect the stock price. The method that used is Logistic Regression Study Method and using Partial Experiments, Simultaneous Experiments and Coefficient Of Determination. The results of the studies show that according to partial only net profit that has a negative impact on stock prices.